APTw combined with mDixon−Quant imaging to distinguish the differentiation degree of cervical squamous carcinoma - Meng, Xing; Tian, Shifeng; Ma, Changjun; Lin, Liangjie; Zhang, Xiaoxiao; Wang, Jiazheng; Song, Qingwei; Liu, Ai Lian (Frontiers in Oncology, 2023)
Background: To investigate the value of amide proton transfer weighted (APTw) imaging combined with modified Dixon quantification (mDixon-Quant) in determining the degree of differentiation of cervical squamous carcinoma (CSC) against histopathologic. Methods: Magnetic resonance imaging (MRI) data (T2WI, mDixon-Quant, and APTw imaging) were collected from 52 CSC patients with information about the degree of differentiation on histopathology. According to histopathologic results, patients were divided into the poorly differentiated group (37 cases) and the well/moderately differentiated group (15 cases). The APTw value by APTw imaging and the fat fraction (FF) and transverse relaxation rate (R2*) values by mDixon-Quant were independently measured by two radiologists. Intra-class correlation coefficients (ICCs) were used to test the consistency of APT, FF, and R2* values measured by the two observers. The Mann-Whitney U test was used to analyze the difference in each parameter between the two groups. Logistic regression analysis was used to assess the association between the degree of differentiation on histopathology and imaging parameters by APTw and mDixon Quant. The ROC curve was used to evaluate the diagnostic efficacy of various parameters and their combinations in distinguishing the degree of CSC differentiation on histopathology. The DeLong test was used to access the differences in the area under the ROC curve (AUC). The Pearson correlation coefficient was used to evaluate the correlation between APTw and mDixon-Quant imaging parameters. Results: The APTw means were 2.95 ± 0.78% and 2.05 (1.85, 2.65)% in the poorly and well/moderately differentiated groups, respectively. The R2* values were 26.62 (21.99, 33.31) /s and 22.93 ± 6.09 /s in the poorly and well/moderately differentiated groups, respectively (P < 0.05). The AUCs of APTw, R2*, and their combination were 0.762, 0.686, and 0.843, respectively. The Delong test suggested statistical significance between R2* and the combination of APTw and R2*. R2* values showed significant correlations with APTw values in the poorly differentiated group. Conclusions: APTw combined with mDixon-Quant can be used to efficiently distinguish the differention degrees of CSC diagnosed on histopathology.